POTENSI PAJAK DAN RETRIBUSI DAERAH DI KABUPATEN YAHUKIMO - Agustinus Nusa; Syaikhul Falah; Ivanna K. Wamafma (Universitas Cenderawasih, 2017)
This research aims to understand how large potential taxes and retribution at the Yahukimo regency. This research using the five taxes and retribution benchmark, namely the growth, economy efficiency, justice, ability to carry out, and conformity as income. By measuring the variables of the potential or not potential in accordance with the specified criteria. The result showed the that variables of economy efficiency, justice, and conformity as income are consistent the taxes and retribution potential in Yahukimo regency. On the variable of economy efficiency concluded that tax charges relatively small, while the threat to the entrepreneurs is the uncertainty neighborhood caused the price increases. Variable of justice concluded that taxes has done in a fair and appropriate with area and the owners capital. Variable of conformity as income is to compare regional regulations with Taxes and Retribution Law, so the results obtained that taxes has in accordance with the rules. While the Growth and the ability to carry out have varying results, taxes and retribution that is quite potentially, potentially or not potentially. Keyword: Growth, economy efficiency, justice, ability to carry out, conformity as income